DUKUNGAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM PEMENUHAN AKTIVITAS SEHARI-HARI DI MASA PANDEMI COVID-19 DI DESA TENGGELA - Euis H. Hidayat; Rona Febriyona; Nurain Mahabu; Jusniati Pua (Jurnal Rumpun Ilmu Kesehatan, 2021)
One of the problems for the elderly during the COVID-19 pandemic is limited mobility due to activities that only take place at home during the pandemic. This causes the daily activities of the elderly to be limited. This study aims to determine the relationship between family support and the independence of the elderly in fulfilling daily activities during the Covid-19 pandemic in Tenggela Village. The research is descriptive correlation type with a cross sectional study approach. The population is the elderly in Tenggela Village, It was concluded that there was a relationship between family support and the independence of the elderly in fulfilling daily activities during the Covid-19 pandemic in Tenggela Village.